HLA‐DQB1*05:239 and ‐DQB1*05:250, were identified by sequencing in Chinese bone marrow donors. (9th June 2021) - Chen, Nanying; Dong, Lina; Wang, Fang; He, Ji; Zhu, Faming
Abstract : Compared with HLA‐DQB1*05:02:01:01, the alleles HLA‐DQB1*05:239 and HLA‐DQB1*05:250 each show one single nucleotide substitution.